Preparation for field work and alumni’s perceptions of work competencies: A correlational study of vocational education graduates - Agisna Mar'Atana; Nurul Amira Fitriani (Priviet Social Sciences Journal, 2026)
This study aims to analyze the effectiveness of Field Work Practice (PKL) orientation in enhancing the work competencies of vocational program alumni. PKL orientation is a preparatory phase before students enter the field, covering work-related materials, professional ethics, and guidelines for conducting the practicum. This research utilizes a quantitative methodology including a descriptive-correlational framework. The sample included 39 graduates of vocational programs chosen by purposive sampling. Data were gathered by an online five-point Likert scale questionnaire and evaluated employing validity tests, reliability assessments, descriptive statistics, and Pearson’s correlation. All instrument items were considered valid. Cronbach’s Alpha scores of 0.953 for the internship preparation variable and 0.939 for the work competence variable indicate an exceptionally high degree of dependability. Descriptive analysis indicates that alumni views of internship preparation are categorized as "very good," with an average score of 4.26, while alumni work competencies are also classified as "very good," with an average score of 4.37. The Pearson correlation analysis yielded a correlation value of 0.67 with a significance level of 0.000 (p < 0.05), indicating a robust and substantial association between internship preparation and alumni work abilities. These findings confirm that structured internship preparation that is relevant to the needs of the workforce contributes positively to improving the work competencies of vocational graduates. Vocational education institutions are recommended to continue improving the quality of field work training, particularly in strengthening professional ethics, communication skills, and adaptability in the workplace. Keywords: field work training, work competencies, vocational education, work readiness, alumni perceptions, experiential learning